Identification of the Factors Affecting the Development of Rural Entrepreneurship in the Study of Kurdistan Province Handicrafts - Moradi, Mohammad Ali; Mousakhani, Morteza; Reshadat Joo, Hamideh (Iranian Journal of Educational Sociology, 2022)
Purpose: Entrepreneurship is considered as the driving force of economic and social growth of societies. Methodology: The present qualitative study is based on grounded theory, while recognizing the dimensions of the rural business space in Kurdistan Province, has identified the factors affecting rural entrepreneurship in this region. Also, in this study, in order to increase the efficiency of policies and plans of rural entrepreneurship development institutions, a conceptual model of extractive factors has been proposed. For this purpose, a group of fifteen rural entrepreneurs, local experts and officials and extra-local experts were selected and studied using non-probability sampling methods, such as theoretical, purposive and snowball sampling. The data were collected using three tools of interview, field observations and review of archival documents and analyzed using open, axial and selective coding. Findings: The study results classified the factors affecting the development of rural entrepreneurship in Kurdistan Province into the following categories: individual, social, cultural, infrastructure, natural and ecological, legal, educational, political and economic institutional factors. Conclusion: In addition, interactive mechanism is reflected according to the structural model of grounded theory with six theoretical components.